Evaluation of initial dosing regimens of vancomycin used in the treatment of infections in patients into a trauma intensive care unit - Milene BRAUN; Rafael LINDEN (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: To verify the exposure to vancomycin in patients admitted to the ICU of trauma from a regional hospital compared to consensos exposure ranges therapy. Methods: Retrospective cross-sectional study, with data collection from electronic medical records of the patients using Vancomycin admitted to the trauma ICU at Hospital Pronto Socorro de Porto Alegre (RS) from January 2022 to May 2022. Results: We evaluated 28 patients who met the inclusion criteria in the study, of these, thirteen (46.42%) presented subtherapeutic trough concentrations of vancomycin, six (21.42%) had therapeutic concentrations and nine (32.14%) had supratherapeutic concentrations. The highest levels of vancomycin occurred between the 2nd and 4th day of treatment. Among the applied attack doses, seven (41.17%) received doses within the recommended range (average of 28.80 mg/kg) and fifteen (53.6%) the initial dose was within the range recommended by international guidelines. Less than 25% of subjects had therapeutic exposure to vancomycin. Conclusion: Therapeutic drug monitoring for vancomycin associated with a pharmacokinetic program that estimates dose adjustments favors the optimization of the therapy, increases the efficiency and benefits of the treatment.